2002
DOI: 10.1152/ajpcell.00613.2001
|View full text |Cite
|
Sign up to set email alerts
|

Na+/H+ exchanger 3 is in large complexes in the center of the apical surface of proximal tubule-derived OK cells

Abstract: Cell biological approaches were used to examine the location and function of the brush border (BB) Na(+)/H(+) exchanger NHE3 in the opossum kidney (OK) polarized renal proximal tubule cell line. NHE3 epitope tagged with the vesicular stomatitis virus glycoprotein epitope (NHE3V) was stably expressed and called OK-E3V cells. On the basis of cell surface biotinylation studies, these cells had 10-15% of total NHE3 on the BB. Intracellular NHE3V largely colocalized with Rab11 and to a lesser extent with EEA1. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
77
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 54 publications
10
77
0
Order By: Relevance
“…We previously showed that NHE3-EGFP localized in OK cells similarly to wild-type, being distributed in the apical membrane and in the juxtanuclear area. It was functionally inhibited by phosphoinositide 3-kinase inhibition (wortmannin), similarly to wildtype studies (Akhter et al, 2002). We have also reported that NHE3-EGFP stably expressed in PS120 cells behaves similarly to wild-type in terms of the percent amount on the surface, basal transport and stimulation by growth factors (Janecki et al, 2000a).…”
Section: Molecularly Engineered Constructssupporting
confidence: 61%
See 1 more Smart Citation
“…We previously showed that NHE3-EGFP localized in OK cells similarly to wild-type, being distributed in the apical membrane and in the juxtanuclear area. It was functionally inhibited by phosphoinositide 3-kinase inhibition (wortmannin), similarly to wildtype studies (Akhter et al, 2002). We have also reported that NHE3-EGFP stably expressed in PS120 cells behaves similarly to wild-type in terms of the percent amount on the surface, basal transport and stimulation by growth factors (Janecki et al, 2000a).…”
Section: Molecularly Engineered Constructssupporting
confidence: 61%
“…The mobile fraction (Mf) of apical NHE3-endosomes, including cellubrevin. NHE3 traffics between these two regions under basal conditions (D'Souza et al, 1998;Akhter et al, 2002). Most rapid regulation of NHE3 appears to involve changes in the amount of BB NHE3, which occurs from changes in the rates of NHE3 trafficking between the BB and the intracellular recycling compartment (Kurashima et al, 1998).…”
mentioning
confidence: 99%
“…Basal NHE3 activity was inhibited by exposure to the PI3K inhibitors, viz. LY594002 (31) and wortmannin (32,33) at low doses, and acutely stimulated NHE3 was reduced by the same inhibitors between 50 and 100% based on the cell type expressing NHE3 and the ligand studied (FGF in PS120 cells by 50% (32); lysophosphatidic acid in opossum kidney cells by 100%) (31). These previous studies of PI3K dependence of basal and acutely stimulated NHE3 activity plus the rapid stimulation of NHE3 activity when PI(3,4,5) 3 was added to the Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been proposed that the trafficking of NHE3 to/from the cell membrane and the juxtanuclear compartment [24] represents a physiologic mechanism by which NHE3 controls Na + /H + exchange in epithelial cells of the kidney, colon, small intestine and gallbladder [25,26]. It also appears that trafficking of NHE3 can be enhanced by NHERF2, apparently via activation of phospholipase C [26].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been proposed that the trafficking of NHE3 to/from the cell membrane and the juxtanuclear compartment [24] represents a physiologic mechanism by which NHE3 controls Na + /H + exchange in epithelial cells of the kidney, colon, small intestine and gallbladder [25,26]. It also appears that trafficking of NHE3 can be enhanced by NHERF2, apparently via activation of phospholipase C [26]. Although the specific physiologic role(s) of NHE3 and NHERF2 in syncytiotrophoblast intracellular function remains to be elucidated, based on our studies we propose that estrogen plays an important role in regulating expression of components of the NHE system within and consequently development and function of the primate placental syncytiotrophoblast.…”
Section: Discussionmentioning
confidence: 99%